(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: This article examines the common difficulties encountered in teaching speaking skills to secondary school students at the A2 level of English proficiency. It explores both linguistic and psychological barriers that hinder students’ ability to express themselves orally, such as limited vocabulary, lack of confidence, fear of making mistakes, and insufficient speaking practice. The study also discusses challenges faced by teachers, including large class sizes, limited classroom time, and lack of resources. Various strategies and practical solutions are proposed to help overcome these issues and improve students’ speaking abilities in a supportive and interactive learning environment.